1982
DOI: 10.1159/000241578
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Analysis of the Postnatal Mouse Pancreas

Abstract: DNA flow cytometry was used to quantitate changes in distribution of cells in each phase of the cell cycle during postnatal development of the mouse pancreas. From birth through day 20 the cells in each phase remained relatively constant, after which there occurred increases in G2-M and S phase cells and a decrease in G₀-G1 phase cells. Polyploidy first became evident at 20 days and increased to 9% by the adult stage at 90 days. The importance of polyploidy is discussed as it may represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…The results for the control tissues agree with previous findings obtained by other methods in showing a higher frequency of polyploid nuclei in the liver (Epstein, 1967; Brodsky & Uryvaeva, 1977, 1985) than in the pancreas (Larsen & Nielsen, 1978; Webb et al. 1982; Ornitz et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results for the control tissues agree with previous findings obtained by other methods in showing a higher frequency of polyploid nuclei in the liver (Epstein, 1967; Brodsky & Uryvaeva, 1977, 1985) than in the pancreas (Larsen & Nielsen, 1978; Webb et al. 1982; Ornitz et al.…”
Section: Discussionsupporting
confidence: 91%
“…Possible beneficial properties of polyploidy include protection against accumulation of recessive mutations or enhanced biosynthetic capability. Polyploid cells often occur in tissues with specialized biosynthetic secretary or storage functions (Brodsky & Uryvaeva, 1977, 1985; Webb et al. 1982), as is the case with the liver, pancreas and corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a high incidence of tetraploid cells in the pancreas of the mouse compared with that of the rat. Webb et al (1982) reported a n incidence of diploid nuclei in the adult mouse pancreas similar to that found in the present study, although those workers considered that most of the remaining nuclei were in S, G2, or M phase. In the present study, the remaining nuclei made up a single symmetrical peak with tetraploid DNA content.…”
Section: Ratsupporting
confidence: 85%
“…In mammals, polyploid cells have been observed in different tissues including the placenta, bone marrow, heart, liver, and pancreas [ 2 , 4 ]. Interestingly, in the pancreas both the endocrine and exocrine cells undergo programmed polyploidization when mice are weaned resulting in a heterogeneous population of cells with different ploidy status [ 4 , 5 ]. The biological significance of polyploid cells in the pancreas is not known.…”
Section: Introductionmentioning
confidence: 99%